EXAMINING STUNTING PREVENTION KNOWLEDGE AMONG HEALTH WORKERS IN RURAL COMMUNITIES OF RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Chronic undernutrition in children remains a global public health concern. In Nigeria, there has been a significant decline in childhood stunting prevalence over the last two decades. However, understanding the factors driving this reduction is crucial for effective interventions. The present study examines stunting prevention knowledge among health workers in rural communities of River State, Nigeria. One hundred six health workers responded to the questionnaire on the knowledge relating to stunting. The findings highlight the critical gaps in health workers’ knowledge and emphasize the need for targeted training and education to enhance their understanding of stunting prevention.